Authentication of Iberian dry-cured ham: New approaches by polymorphic fingerprint and ultrahigh resolution mass spectrometry. (February 2016) - Bayés-García, L.; Tres, A.; Vichi, S.; Calvet, T.; Cuevas-Diarte, M.A.; Codony, R.; Boatella, J.; Caixach, J.; Ueno, S.; Guardiola, F.
Abstract: Foods with high added value, such as Iberian dry-cured products, are susceptible to fraud. Many attempts have been made to differentiate the commercial/quality categories of Iberian dry-cured hams by analytical determinations. However, as discrimination by such means is not fully reliable, legislation to prevent fraudulent practice is based on administrative controls and certification. Here, new analytical approaches based on ultrahigh resolution mass spectrometry (UHRMS) and crystallographic techniques applied to the lipid fraction, in combination with chemometrics, are studied. The results of the triacylglycerol profile determined by UHRMS and the fingerprint provided by the thermograms obtained by differential scanning calorimetry offer the promise of analytic discrimination of Iberian dry-cured ham categories. In addition, these determinations, in combination with chemometrics, may prove extremely useful to authenticate many foods containing high to moderate amounts of lipids. Highlights: New analytical approaches applied to lipid fraction were assayed to authenticate Iberian dry-cured ham. Chemometrics was applied to analytical data to discriminate Iberian dry-cured ham categories. Triacylglycerol profile determined by UHRMS is a promising approach for discrimination. Fingerprint provided by thermograms from DSC is a promising approach for discrimination. These approaches may prove extremely useful to authenticate many foods containing high to moderate amounts of lipids.